Validation of the new version of the Minimal Documentation System (MIDOS) for patients in palliative care: The German version of the Edmonton Symptom Assessment Scale (ESAS) Validierung der neuen Fassung des Minimalen Dokumentationssystems (MIDOS2) für Patienten in der Palliativmedizin : Deutsche Version der Edmonton Symptom Assessment Scale (ESAS) - Stiel, S.; Matthes, M. E.; Bertram, L.; Ostgathe, Christoph; Elsner, F.; Radbruch, L. (Schmerz, 2010)
Background: Repeated self-assessment of symptoms and problems of patients is required for quality assurance in palliative care. In Germany, the Minimal Documentation System (MIDOS) has been designed specifically for palliative care patients. To adapt MIDOS as a German version of the Edmonton Symptom Assessment Scale (ESAS) a revised version of MIDOS2 has now been validated. Two original items on average and highest pain intensity (11-step NRS) were replaced by one item on pain intensity on a 4-step VRS and the assessment of vomitus, lack of appetite and depressive mood were added to the assessment of nausea, dyspnoea, constipation, weakness, tiredness, anxiety, others and well-being which were already part of the original version. Method: All patients admitted to the palliative care unit were asked to participate voluntarily in this study. MIDOS2, the German versions of the ESAS and the quality of life questionnaire EORTC QLQ-C15-Pal were completed on the same day during their inpatient stay. MIDOS2 was repeated on the next day. Results: From August 2009 to March 2010, 60 patients (55% men, 45% women; mean age = 64.3, range = 23.6-92.4 years) treated in the palliative care unit completed the study. Self-assessment with MIDOS2 was reported to burden the patients only slightly (mean burden = 1.1, range: 0 = no to 10 = maximum burden on a NRS), application of MIDOS2 took between 1 and 7 min (mean duration = 2.4 min) and 61.7% of the patients preferred MIDOS2 (with VRS) to ESAS (30%) (with NRS) for routine daily documentation. External criterion validity by inter-item correlations of MIDOS2 with ESAS varied between r = .533 (anxiety) and .881 (nausea) and between r = .348 (depressive mood) and .717 (constipation) for the corresponding items of the EORTC QLQ-C15-Pal. Test-retest reliability between the sum scores of symptoms and problems reported in MIDOS2 on the first day and on the second day was .688, and r = .573 for well-being. Conclusion: MIDOS2 can be recommended for routine daily documentation in palliative care because of low burden, little expenditure of time and high participation of patients. Statistical evaluation indicated good external validity and reliability. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2025-10-27
Keywords: Burden; Self-assessment; Symptom frequency; Symptom intensity